Piano Sonata no. 9 in E major, op. 14, no. 1, published by Brandus - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Brandus et Cie.; Paris; France, 2024)
Reprint of the Piano Sonata no. 9 in E major, op. 14, no. 1, by Brandus & Cie., reprinted from the plates of M. Schlesinger.